Representação simbólica da tatuagem e seu significado - Lessa, Ludmilla López (2017)
This research aimed to investigate the current representations of tattoos and to make a symbolic analysis of them. Therefore, it was selected 30 individuals through the procedure of Snow Ball (15 men and 15 women), aged between 22 and 40, who had at least 30% of their body surface covered by tattoos. On data collection, it was utilized a semi-directed interview, a picture of a chosen tattoo by the participant and the free association from this image. The data were analyzed according to the jungian psychosomatics. The results allowed to observe 11 categories: perception of aching, rising self-esteem, rising of attractiveness feeling, prejudices, regret on the choice of the image, religious factor, financial independency, moment of life they made the chosen tattoo, motivation for acquisition of the chosen tattoo, repercussion on the individual’s life after making the tattoo, symbols and images chosen. The results pointed out the incidence of prejudice, influence of the religious and financial factor at the time of tattooing, besides the perception of pain sometimes related to sacrifice, sometimes associated to self-mutilation behaviours. It was observed that the tattoo increases the self-esteem and eases extroversion on social relationships. It can be said that unconscious contents are transducted to skin through the tattoo. It is concluded that body marks help the individual on the appropriation of his own identity, contribute to the organization of psychological conflicts, and act as an important component on rites of passage. Finally, the tattoo can promote the self-knowledge